An Evolutionary Perspective on Yeast Mating-Type Switching. Issue 1 (1st May 2017) - Hanson, Sara J; Wolfe, Kenneth H
Abstract: Cell differentiation in yeast species is controlled by a reversible, programmed DNA-rearrangement process called mating-type switching. Switching is achieved by two functionally similar but structurally distinct processes in the budding yeast Saccharomyces cerevisiae and the fission yeast Schizosaccharomyces pombe . In both species, haploid cells possess one active and two silent copies of the mating-type locus (a three-cassette structure), the active locus is cleaved, and synthesis-dependent strand annealing is used to replace it with a copy of a silent locus encoding the opposite mating-type information. Each species has its own set of components responsible for regulating these processes. In this review, we summarize knowledge about the function and evolution of mating-type switching components in these species, including mechanisms of heterochromatin formation, MAT locus cleavage, donor bias, lineage tracking, and environmental regulation of switching. We compare switching in these well-studied species to others such as Kluyveromyces lactis and the methylotrophic yeasts Ogataea polymorpha and Komagataella phaffii . We focus on some key questions: Which cells switch mating type? What molecular apparatus is required for switching? Where did it come from? And what is the evolutionary purpose of switching?